Parameter optimization and test based on discrete element method for biaxial layered cutting and deep rotary tillage process in rice stubble fields - Zhang, Yifu; Shi, Wen; Zhou, Huini; Zheng, Xiaogang (International Journal of Agricultural and Biological Engineering, 2025)
Straw incorporation into farmlands is recognized as beneficial for improving cultivated land quality, stimulating soil carbon sinks, and promoting crop growth. However, in the rice-wheat double-cropping system, the postharvest period results in abundant crop straw, leading to prominent straw surplus issues. Problems such as the tight schedule between harvesting and sowing and high-quality requirements for seedbeds result in traditional rotary tillage, which often results in excess straw in the tillage layer and straw piles, severely restricting sowing quality. To address these issues, a technological solution was proposed involving biaxial layered cutting for deep rotary tillage and uniform mixing of straw. The focus was on the biaxial deep rotary tillage and uniform mixing processes, along with device testing in paddy fields, via the discrete element method. A composite discrete element model of root stubble, soil, and rice straw was established for a typical rice-wheat rotation area in Jiangsu Province, China, and coupled with a biaxial rotary tillage unit. Using the response surface analysis method, the vertical height difference of the rear cutter shaft relative to the front cutter shaft (Ln), the rotation speed of the cutter group (w), and the forwards speed of the unit (v) were considered the three factors affecting rotary tillage quality. A three-factor, three-level orthogonal simulation test was conducted, yielding the optimal parameter combination: Ln = –73.3 mm, w = 273.6 r/min, and v = 0.6 m/s. Under this combination, the tillage performance achieved a total power consumption of 29.66 kW and a straw burial rate of 94.6%. The results of the prototype field test indicated that the biaxial rotary tillage device significantly loosened the top 20 cm of the soil layer, with a post-tillage surface flatness of 2.80 cm, a straw burial rate of 92.6%, and a tillage depth stability of 95.3%, meeting the quality requirements for the incorporation of straw rotary tillage. The results of this study can provide a theoretical basis and case reference for achieving high-quality mechanized straw incorporation in rice-wheat rotation systems. Keywords: straw returning, discrete element method, biaxial deep rotary tillage, parameter optimizationDOI: 10.25165/j.ijabe.20251805.9300Citation: Zhang Y F, Shi W, Zhou H N, Zheng X G. Parameter optimization and test based on discrete element method for biaxial layered cutting and deep rotary tillage process in rice stubble fields. Int J Agric & Biol Eng, 2025; 18(5): 171–180.